Legal protection OF registered marks (juridical analysis OF court decision number 2/pdt.sus.hki/merek/2020/pn niaga medan) - Simbolon, Yolanda; Deo, Ivania; Pakpahan, Marlina; Noor, Tajuddin (Journal of Law Science, 2024)
Trademark rights are one type of Intellectual Property Rights which differentiates the origin of the goods and services. The existence of this protection shows that the state is obliged to enforce brand law, such as protecting registered brands. This type of research is normative legal research. Normative research is doctrinal law where law is often conceptualized as what is written in regulations. Legislation (Law in book) or laws decided by judges through the court process. Decision Number 2/Pdt.Sus.HKI/Merek/2020/PN Niaga Mdn confirms that the Plantiff's Goat Brand must be legally protected until 2025. By having a “GOAT BRAND” brand certificate, the Plantiff deserves exclusive rights protection of ownership and use of the brand. In this decision, the judge found similarities between the brands “GOAT BRAND” and “2 GOATS”, as well as the bad fath of the Defendant. The judge also referred to the principle of the first to file system in brand law in Indonesia so that the Plantiff deserves to get protection of exclusive rights to ownership and use of the mark.